620 Daycase Appendicectomy and Same Day Discharge After Laparoscopic Appendicectomy. (12th October 2021) - Gumaa, D; Shrestha, S; Jenner, D
Abstract: Introduction: Laparoscopic appendicectomy (LA) is the most common emergency surgical operation. Recently Same day discharge after uncomplicated LA has been more popular. Our study has sought to assess the safety of same day discharge and creating a pathway for day case appendicectomy. Inclusion Criteria: Pre-operative: No signs of sepsis. CT proven or clinically suspected mild appendicitis (WCC<15, CRP<150) Intra-operative: Mild appendicitis, No perforation, No Gangrene, No free pus. Post-operative: Pain is controlled with oral analgesia. Patient is tolerating oral intake. No need for post-operative antibiotics according to WSES Jerusalem Guideline for diagnosis and treatment of acute appendicitis 2016. Social circumstances do allow safe discharge. Method: A prospective case series study was undertaken at a large district general hospital over a 9-month period. 27 patients were included in the study, age range (10-78) years. 74% had ASA 1. 8 patients underwent day case LA & were sent home on oral antibiotics the day before the operation and asked to come back the following morning. 22 patients did not require any post op antibiotics. 5 patients received 1 dose of IV antibiotics post-operative. The 30-day morbidity/ mortality were zero. There were no readmissions during this time and patient satisfaction was high. Conclusions: Same day discharge after laparoscopic appendectomy is safe and valid. Day case appendectomy should be considered for appropriate patients. Both approaches will decrease patients' risk of hospital acquired infection and also decrease the burden on the NHS.